Comparison of Stromal Vascular Fraction and Adipose-Derived Stem Cells for Protection of Renal Function in a Rodent Model of Ischemic Acute Kidney Injury - Joomin Aum; Myoung Jin Jang; Yu Seon Kim; Bo Hyun Kim; Dong Hyeon An; Jae Hyeon Han; Nayoung Suh; Choung-Soo Kim; Dalsan You (Stem Cells International)
Aims. Few studies have compared the use of different cell types derived from adipose tissue or the optimal route for efficient and safe cell delivery in ischemic acute kidney injury (AKI). We compared the abilities of stromal vascular fraction (SVF) and adipose-derived stem cells (ADSC), injected via three different routes, to protect renal function in a rodent model of ischemic AKI. Methods. Ninety male Sprague-Dawley rats were randomly divided into 9 groups: sham, nephrectomy control, AKI control, transaortic renal arterial SVF injection, renal parenchymal SVF injection, tail venous SVF injection, transaortic renal arterial ADSC injection, renal parenchymal ADSC injection, and tail venous ADSC injection groups. Their renal function was assessed 4 days before and 1, 2, 3, 4, 7, and 14 days after surgical procedures to induce ischemic AKI. The histomorphometric studies were performed 14 days after surgical procedures. Results. Renal parenchymal injection of SVF notably reduced the level of serum blood urea nitrogen and creatinine elevation compared to the AKI control group. Renal parenchymal injection of SVF notably reduced the level of creatinine clearance decrease. In addition, collagen content was lower in the renal parenchymal SVF injection group, and fibrosis was reduced. Apoptosis was reduced in the renal parenchymal SVF injection group, and proliferation was increased. The expression levels of antioxidative markers such as glutathione reductase and peroxidase were higher in the renal parenchymal SVF injection group. Conclusions. Our findings suggest that renal function is protected from ischemic AKI through renal parenchymal injection of SVF, which has enhanced antifibrotic, antiapoptotic, and antioxidative effects.